Ustaz Ebit Lew shares the secret to success with UMP residents - Nor Salwana, Mohammad Idris (2021)
PEKAN, 3 May 2021 – “Our lives will be more meaningful by bringing happiness and joy to others. “Be a person who is good, sincere, hardworking, never gives up and patient, insya-Allah one day you will surely succeed,” said Ustaz Ebit Lew during the UMP Professional Talk Series titled ‘Community Development Through Social Entrepreneurship’ that was broadcasted live online via Facebook recently.